Mind and Body: Italian Validation of the Postural Awareness Scale - Topino, Eleonora; Gori, Alessio; Cramer, Holger (Frontiers in Psychology, 2020)
Postural awareness (PA) refers to a subjective conscious awareness of body posture and falls within the framework of mind-body integration. The aim of this research was the validation and the evaluation of psychometric properties of the Postural Awareness Scale (PAS) in an Italian population sample (n=928; 45.04% men and 54.96% women; mean age= 29.96 years, SD=11.44). The results obtained with Velicer’s Minimum Average Partial Test (MAP), Horn’s Parallel Analysis (HPA) and Exploratory Factor Analysis (EFA) showed a two-factor solution, as supported by the Confirmatory Factor Analysis (CFA): Ease/Familiarity with Postural Awareness and Need for Attention Regulation with Postural Awareness. Furthermore, the findings highlighted both a good internal consistency (α= .76 for the total scale and α= .80, α= .79 for the two subscales) and a satisfactory construct validity. Furthermore, MANOVA was carried out to assess differences in postural awareness between specific sub-group. In particular, the positive effects of physical activity and healthy body weight were confirmed, while no significant differences related to gender or age were found. All these findings suggest that the Italian version of the PAS is a rapid instrument with good psychometric properties, which can be useful both for research and clinical practice.